Komunikasi Mitigasi Bencana Berbasis WhatsApp dan QR Code: Systematic Literature Review tentang Sinergi Pemerintah Lokal dan Masyarakat: Systematic Literature Review tentang Sinergi Pemerintah Lokal dan Masyarakat - Aulya Defrinia Cita; Ardieansyah Ardieansyah; Wenty Zahrati (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2026)
This study aims to analyze the utilization of WhatsApp and QR Code in disaster mitigation communication and to formulate a five-layer synergy model between local governments and communities based on digital technology. The method employed is a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework. Literature searches were conducted across four academic databases namely Google Scholar, Scopus, ScienceDirect, and SINTA between 16–22 April 2025, covering publications from 2020 to 2025. From 200 identified articles, 8 duplicates were removed and 192 articles entered the screening phase. Subsequently, 138 articles were excluded through title and abstract screening, yielding 54 articles for full-text assessment, of which 35 were excluded, resulting in 19 articles that met all inclusion criteria and were analyzed using narrative and thematic synthesis. Three principal findings emerged. First, there is an accelerative upward trend in scientific publications on messaging-platform use in disaster mitigation, peaking at seven articles in 2025. Second, WhatsApp has proven effective as a real-time disaster communication platform that supports community-based preparedness education and integration with IoT-based early warning systems. Third, a significant research gap exists regarding the role of QR Code in disaster communication systems, although QR Code adoption has been documented in adjacent sectors. Based on the synthesis, a five-layer synergy model is formulated, encompassing: (1) contextual root causes, (2) digital synergy platforms, (3) synergy mechanisms, (4) key challenges, and (5) policy recommendations. The novelty of this study lies in the formulation of the five-layer synergy model that integrates real-time communication channels based on WhatsApp, rapid information access based on QR Code, institutional governance of local governments, and community participation within a single disaster mitigation communication framework. This model transcends technocentric approaches by positioning institutional governance and community participation as key determinants of effectiveness, offering a replicable policy framework for local governments in disaster-prone areas.